Nazi justiz law of the Holocaust - Miller, Richard Lawrence (Praeger, 1995)
Death camps are the most enduring image of the Holocaust, but they were only the final expression of a destruction process that began in 1933. In that year the Nazi regime mobilized members of an entire society to destroy their neighbors. Lawmakers, judges, attorneys, and the rest of the legal system played a crucial role in reassuring "good Germans" that a war on Jews was legitimate. Using original decrees, court decisions, and first-hand recollections of participants, Nazi Justiz documents how the German legal system transformed itself into a criminal organization. We also see not only how the legal system shaped everyday life, but how good Germans and the business community benefited from the Holocaust. Germany in the 1930s - before the war - is emphasized. Such emphasis demonstrates that a Holocaust can happen in any country sharing the heritage of Western civilization, and warns of the inevitable outcome once ordinary people are targeted in a process of destruction.
Keywords: Geschichte 1933-1945; Geschichte 1939-1945; Holocaust; Juridische aspecten; Geschichte; Juden; Judenvernichtung; Holocaust, Jewish (1939-1945) -- Germany; Jews -- Legal status, laws, etc. -- Germany -- History; National socialism; Recht; Nationalsozialismus; Deutschland